L’architettura industriale del Novecento come archeologia della contemporaneità - Parisi, Roberto (OS. Opificio della Storia, 2020)
The essay proposes the 20th industrial architecture as a topic of particular importance in the context of studies on processes and practices of the legitimation and protection of cultural heritage of the contemporary age. Through a brief historical summary of the evolution of the factory during the Twentieth Century, the author tackles the topic in a glocal perspective, highlighting the need to overcome a western-centred reading and to consider the physical remains of the world industrial heritage as an opportunity to transmit to future generations not only the history of the great productive and technological primates reached by humanity, but also the history of social conflicts, of environmental dramas, of political and cultural failures.